Perbaikan Sifat Kimia Lahan Bekas Tambang Emas Melalui Aplikasi Biochar Sekam Padi dan Pupuk Kandang Ayam - PANJI ROMADHAN; GUSMINI GUSMINI; HERMANSAH HERMANSAH (Fakultas Pertanian Universitas Udayana, 2022)
Improvement of Chemical Properties of Ex-Gold Mine Land Through Application of Rice Husk Biochar and Chicken Manure. Ex-gold mining land that have been degraded so that soil fertility is very low. Mining with an open system causes an increase in the oxidation of sulfuric minerals which reduces nutrient levels, so it is necessary to make efforts to increase nutrients through the addition of rice husk biochar and manure. The purpose of the study was to determine the role of rice husk biochar and manure to improve soil chemical properties. This study used a completely randomice design (CRD)with 6 treatments and 4 replications. The results showed that 100% manure treatments could increase soil fertility, when the soil pH was 6.28, total N 0.0072%, and available P 59.74 ppm. The best treatments for the organic C parameter is a combination of 50% rice husk biochar + 50% manure, which is 1.42%. Based on research, the addition of organic matter can improve the chemical properties of ex-gold mining land.